2019
DOI: 10.1021/acs.macromol.9b02030
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Cross-Linkable Polymer Inks for Solution-Based OLED Fabrication

Abstract: We introduce a catalyst-free, highly efficient, ambient temperature Diels−Alder reaction employing omethylbenzaldehyde derivatives as photocaged dienes as an ideal approach for forming three-dimensional insoluble networks for inkjet printing of OLED emissive layer. Herein, poly(methyl methacrylate) based polymers containing 4-(9H-carbazol-9-yl)-2-(3′-hydroxy-[1,1′-biphenyl]-3-yl)isoindoline-1,3-dione as a blue-green (λ max = 495−500 nm) thermally activated delayed fluorescence (TADF) emitter and a photochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…For a multi-layer deposition, usually, non-orthogonal solvents are preferred; however, organic compounds have a similar chemical structure; therefore, it is challenging to find orthogonal solvents. Hence, there are many opportunities to develop crosslinkable materials 111,112 and/or solvent switching materials 64 , eliminating the need for orthogonal solvents.…”
Section: Slot-die Oleds Vs Oleds Made By Other R2r Solution-based Tementioning
confidence: 99%
“…For a multi-layer deposition, usually, non-orthogonal solvents are preferred; however, organic compounds have a similar chemical structure; therefore, it is challenging to find orthogonal solvents. Hence, there are many opportunities to develop crosslinkable materials 111,112 and/or solvent switching materials 64 , eliminating the need for orthogonal solvents.…”
Section: Slot-die Oleds Vs Oleds Made By Other R2r Solution-based Tementioning
confidence: 99%
“…For example, the utilization of orthogonal solvents enables the patterning of different organic materials on an identical substrate, while the damage issue in multiple processing cannot completely avoid. [ 27,28 ] Exploiting the cross‐linkable luminescent polymer to enhance solution stability allows the successive solution processing of multicolor light‐emitting devices; [ 5,29–32 ] unfortunately, the complicated chemical synthesis of these cross‐linkable functional materials significantly limits the material choice for full‐color microlasers. [ 33,34 ] Therefore, developing a robust approach that does not depend on chemical synthesis to integrate pixelated full‐color microlaser arrays is necessary for next‐generation flat‐panel laser displays.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdavian et al have incorporated the spiropyran chromophore into flexible acrylic copolymers for the preparation of dual-stimuli-responsive polyacrylic nanofibers via electrospinning, which can be used as smart platforms for reversible real-time data storage with enhanced photostability as well as improved response time by alternant acid/base vapors or UV/vis stimulations . Notably, maleimide and its derivatives have attracted great attention in developing stimulus-responsive material systems with simple molecular structures. Through a simple synthetic strategy, such as the Diels–Alder reaction, a series of multi-stimuli-responsive polymer brushes or smart copolymers with tunable fluorescence properties have been fabricated. , Natural and synthetic polymers fabrics, such as cotton fabrics, as cost-effective three-dimensional scaffolds with various programmable surface functional modifications, have been extensively applied in oil/water separation, biomedicine, electrical device field, sensing, and artificial intelligence. For instance, Zhu et al have fabricated smart Janus textile with adaptive moisture/thermal management by spray coating combined with in situ cross-linking of thermoresponsive moieties onto different sides of cotton fabric . Wang et al have reported simultaneous enhancement of stain removal and comfort control in cotton fabrics via surfaces decorated with cross-linked light and thermal dual-responsive copolymers .…”
Section: Introductionmentioning
confidence: 99%